Mechanistic Insights Into Hepatotoxicity‐Induced Liver Cirrhosis and Anemia: Iron Dysregulation, the Hepcidin–Ferroportin Axis, and Emerging Therapeutic Strategies - Debabrata Dash; Raj Kumar Koiri (Organ Medicine, 2026)
ABSTRACT Patients with alcohol‐associated liver cirrhosis or acetaminophen (APAP) toxicity frequently develop anemia accompanied by disturbances in iron metabolism. Dysregulation of hepcidin–ferroportin signaling, together with other factors such as inflammation, oxidative stress, hypoxia, impaired intestinal iron absorption, malnutrition, and gastrointestinal bleeding, contributes to the pathogenesis of anemia in patients with chronic liver disease. Alcohol‐ and APAP‐induced liver injury involves interconnected mechanisms, including oxidative stress, mitochondrial dysfunction, inflammation, and fibrosis. In this review, we explore the relationship between alcohol‐ and APAP‐induced hepatotoxicity, anemia, and iron dysregulation, with a focus on hepcidin‐ferroportin signaling and the regulation of hepcidin and ferroportin by inflammatory, hypoxic, erythropoietic, and iron‐dependent signals. Moreover, the development of iron deficiency and iron overload at different stages of alcoholic liver disease, as well as the roles of folate metabolism, intestinal iron absorption, the gut microbiota, erythropoietin, and erythroferrone, and the contribution of anemia‐associated hypoxia to liver injury, are discussed. Conventional treatments, including ferrous salts and folic acid, as well as emerging therapies targeting hypoxia‐inducible factor signaling, hepcidin–ferroportin signaling, intravenous iron therapy, and erythropoiesis, are discussed. The potential interaction between iron supplementation and APAP‐induced hepatotoxicity is also addressed. Finally, current knowledge gaps and promising therapeutic directions for the management of hepatotoxicity‐associated anemia are highlighted.